2017
DOI: 10.1021/acs.joc.7b01647
|View full text |Cite
|
Sign up to set email alerts
|

A Naphtho-p-quinodimethane Exhibiting Baird’s (Anti)Aromaticity, Broken Symmetry, and Attractive Photoluminescence

Abstract: We report a novel reductive desulfurization reaction involving π-acidic naphthalene diimides (NDI) 1 using thionating agents such as Lawesson's reagent. Along with the expected thionated NDI derivatives 2-6, new heterocyclic naphtho-p-quinodimethane compounds 7 depicting broken/reduced symmetry were successfully isolated and fully characterized. Empirical studies and theoretical modeling suggest that 7 was formed via a six-membered ring oxathiaphosphenine intermediate rather than the usual four-membered ring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 66 publications
3
39
0
Order By: Relevance
“…For the reaction depicted in Scheme , we hypothesize that the reaction pathway leading to QDM 2 (and 3 ) could also produce the thermodynamic regio‐isomers, where the thiocarbonyl groups are outside the fjord of the π‐expansion: a comprehensive mechanistic rationale is depicted in the Supporting Information (Figure S18). Nonetheless, on the basis of our previously reported mechanistic rationale (for QDM 1 ) and additional computational data, it was found that the pathway to form the doubly de‐aromatized phosphinine intermediate(s) that would lead to the regio‐isomers of 2 (and 3 ) is kinetically not favored.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For the reaction depicted in Scheme , we hypothesize that the reaction pathway leading to QDM 2 (and 3 ) could also produce the thermodynamic regio‐isomers, where the thiocarbonyl groups are outside the fjord of the π‐expansion: a comprehensive mechanistic rationale is depicted in the Supporting Information (Figure S18). Nonetheless, on the basis of our previously reported mechanistic rationale (for QDM 1 ) and additional computational data, it was found that the pathway to form the doubly de‐aromatized phosphinine intermediate(s) that would lead to the regio‐isomers of 2 (and 3 ) is kinetically not favored.…”
Section: Resultsmentioning
confidence: 94%
“…We recently demonstrated that the fusion of a p ‐QDM unit to a phenylene ring can generate a new naphthoquinodimethane chromophore 1 (Figure ) which exhibits unusual ground and excited state aromaticity and photophysical properties . Our previously reported quinoidal chromophore can also be employed as a light‐harvesting triplet sensitizer for photonic research such as triplet–triplet annihilation photon upconversion .…”
Section: Introductionmentioning
confidence: 98%
“…For example, several reports demonstrate that aromatic and antiaromatic character drive reactivity in excited states and therefore can be used to describe and predict photochemical reactions [24–30] . Additionally, new functional materials have been designed by using the concept of excited‐state aromaticity and antiaromaticity as a strategy to modulate the singlet–triplet (S–T) energy gap, [20, 31, 32] which is relevant to organic electronics, [32–34] photoswitching, [35, 36] photoluminescence, [37] and singlet‐fission [33, 38–40] capable materials. One possible avenue to modulate the S–T gap is through the use of compounds with “adaptive aromaticity”, which are aromatic in both the ground state and the excited state, such as metallopentalenes [41, 42] or aromatic chameleons [43–45] …”
Section: Introductionmentioning
confidence: 99%
“…We had previously employed QDM as a Baird‐type heavy‐atom‐free aromatic triplet chromophore to sensitize polyaromatic hydrocarbons and achieved triplet–triplet annihilation based photon upconversion (TTA‐UC) (16–18). Dipyrrolonaphthyridine‐dione ( DPND ), the precursor of I 2 – DPND, was first reported by Gryko and Kozankiewicz (19) and later utilized by Wang, Zhu and Fu to achieve singlet fission (SF) in the solid state (20).…”
Section: Introductionmentioning
confidence: 99%